José María Lacarra and the history of Navarre - de la Cruz Herranz, Luis Miguel de la Cruz Herranz (Huarte de San Juan. Geografía e Historia, 2017)
This article delves into the figure of José María Lacarra as historian of Navarre. The author provides new details about his biography and university studies and contextualizes his extensive bibliographical production on Navarre’s history in many of his facets: Middle and Modern Age, History of Art, Philology and History of Law and Institutions.
Keywords: José María Lacarra; history of Navarra; history of law; historiography